Theileria parva: Sporozoite entry into bovine lymphocytes is not dependent on the parasite cytoskeleton - Shaw, M.K. (Elsevier, 1999)
The main conclusion from the present study is that T. parva sporozoite entry is dependent on a functional host cell actin cytoskeleton and is not driven by the parasite. Treating lymphocytes with cytochalasin D resulted in a dose-dependent reduction in the levels of host cell infection. However, the primary effect was to block sporozoite binding and only at the highest concentration (20 muM) was sporozoite internalization significantly reduced. In fact at lower concentrations (1-10 muM) cytochalasin treatment lead to a relative increase in sporozoite internalization. The results are consistant with sporozoite entry being primarily a possibe process and with a functional host cell actin cytoskeleton that is required only to maintain the molecular integrity of the surface membrane. Thus T. parva sporozoite entry differs from the process in other apicomplexans, although the results are consistent with a number of features of sporozoite biology. Treatment of lymphocytes with either the microtubule-destablizing agent, nocodazole, or taxol, which induces microtubule polymerization, had no significant effect on sporozoite binding or entry. As both reagents had the expected effects on the lymphocyte microtubule system it is unlikely that host cell microtubules are essential for successful sporozoite invasion or establishment.